Living Qur’an Pesantren: The Process and the Background of Khataman Al-Qur’an Tradition - Yeniati Ulfah; Edi Kurniawan Farid (Santri: Journal of Pesantren and Fiqh Sosial, 2023)
The tradition of khataman al-Qur’an is vital for students, alumni, and Zainul Hasan Genggong Pesantren followers. This tradition is held every haul of the Kiai. This study aims, First, to explain how the process of the khatam al-Qur’an tradition held by students, alumni, and followers of the Zainul Hasan Genggong Pesantren. Second, to find out the background of Khataman al-Qur’an tradition. This research is qualitative research using ethnographic studies. Data collection techniques using participatory observation, in-depth interviews, and documentation. Data analysis uses the Miles and Huberman model, known as data reduction, data presentation, and conclusion. To find out the validity of data using triangulation techniques, combining source and technique triangulation. The research results are as follows; first, the khataman al-Qur’an Tradition among students is held togetherly through three stages, pre-ceremony, ceremony, and post-ceremony. Meanwhile, among alumni and followers, the process of khataman al-Qur’an is held offline and online, coordinated by Alumni organizations known as the Zainul Hasan Pesantren Alumni and Santri Association (Tanaszaha). Second, the background of Khataman al-Qur’an tradition is based on the al-Qur’an, al-Hadith, Qoul 'ulama,' and is inspired by other Pesantren ceremonies.